Addressing marine litter through sustainable tourism: The case of the Siargao Islands in the Southern Philippines - Kevin Roy B. Serrona; Jeongsoo Yu; Mary Jean A. Camarin (Asian Development Bank Institute (ADBI), 2022)
Marine litter seriously affects island-based or archipelagic economies. The Philippines is an example of a country at the center of this predicament due to its strategic geographic location as a regional trade route. Urbanization, rapid economic development, and the population increase are some of the key factors contributing to increased consumption and waste generation. Tourism is one of the main economic drivers, with several pristine islands serving as leisure destinations for local and international visitors. In fact, 8 million tourists visited the country in 2019, which contributed 12% to the country's GDP and provided 5.4 million jobs. However, tourism is under threat from locally generated waste materials and those reaching the shores from international waters. One of the most popular tourism destinations is the Siargao Islands, which earned the top spot in the Best Holiday Destination in 2020 of Conde Nast, a prestigious international travel magazine. The island is well known for its annual international surfing and game fishing competitions. It is pursuing sustainable tourism because of the increasing number of tourists along with the alarming increase in waste generation. The island faces the Pacific Ocean and receives marine debris that yearly monsoon winds bring. This paper aims to explore marine litter mitigation and prevention in tourism destinations like Siargao through circular economy interventions. Innovative legislation and policies, capacity building, deposit refund systems, technological innovations, and community-based approaches to minimize, capture, and process marine litter are some of the key areas that it will tackle in the hope of contributing to the global practices on sustainable tourism in island economies.
Keywords: Z3; 330; Sustainable tourism; circular economy; marine litter; participatory governance; international cooperation